2013
DOI: 10.1002/jrsm.1094
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for identifying cross-disciplinary and ‘hard-to-detect’ evidence for systematic review

Abstract: Driven by necessity in our own complex review, we developed alternative systematic ways of identifying relevant evidence where the key concepts are generally not focal to the primary studies' aims and are found across multiple disciplines-that is, hard-to-detect evidence. Specifically, we sought to identify evidence on community engagement in public health interventions that aim to reduce health inequalities. Our initial search strategy used text mining to identify synonyms for the concept 'community engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…O'Mara‐Eves et al observed that a small challenge is deciding on the threshold below which terms identified by Termine would not be considered, and they used a threshold C‐value of 5 when analysing the full text of 5 papers. Their rationale was that “it was the common value below which mined terms seemed to lose relevance across the five papers” (p. 53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O'Mara‐Eves et al observed that a small challenge is deciding on the threshold below which terms identified by Termine would not be considered, and they used a threshold C‐value of 5 when analysing the full text of 5 papers. Their rationale was that “it was the common value below which mined terms seemed to lose relevance across the five papers” (p. 53).…”
Section: Discussionmentioning
confidence: 99%
“…The data included in sample are also important to consider. In the examples here, citations and abstracts were used; however, O'Mara‐Eves et al used the full‐text of 5 papers that were seminal within the area of their search focus. In some cases, the use of full‐texts may not always be possible (for example, limitations in the software, or a lack of known relevant studies) or it might be too inefficient to make the process worthwhile, given that retrieving and then the processing the full‐text documents may add considerable time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, where the topic for review cuts across disciplines, different terminologies may be used (O'Mara-Eves et al, 2014). Similarly, Littell (2006) reported that search strategies that worked for her UK colleagues needed adaptation in North America.…”
Section: Search Methods and Data Retrievalmentioning
confidence: 99%
“…As a result, a growing number of librarians and informatics practitioners have suggested the use of analytics to facilitate this process. Many of these suggestions involve the use of text mining and topic modeling to automatically generate search queries to identify relevant documents (Aphinyanaphongs, Tsamardinos, Statnikov, Hardin, & Aliferis, 2005;Hausner, Waffenschmidt, Kaiser, & Simon, 2012;O'Mara-Eves et al, 2014) or to categorize the retrieved documents to facilitate the literature screening process (Adeva, Atxa, Carrillo, & Zengotitabengoa, 2014;Bekhuis & Demner-Fushman, 2012;Frunza, Inkpen, Matwin, Klement, & O'Blenis, 2011;Shemilt et al, 2014;Wallace, Trikalinos, Lau, Brodley, & Schmid, 2010). For overviews of text mining applications in systematic reviews, see Thomas, McNaught, and Ananiadou (2011); Lefebvre, Glanville, Wieland, Coles, and Weightman (2013); and O'Mara-Eves, Thomas, McNaught, Miwa, and Ananiadou (2015).…”
Section: Introductionmentioning
confidence: 99%